Event and abyss. Critical dialogue between Heidegger and Deleuze - Esperón, Juan Pablo E. (Anales del Seminario de Historia de la Filosofía, 2018)
In the present article we propose to approach and think about the event, the difference and the abyss. This is extremely important because it allows us to think about the individuation of the new. For this, we expose the positions of Heidegger and Deleuze. In the conclusions, we try to make dialogues both philosophies so that they are pushing each other trying to avoid justifying one position over the other.
Keywords: event; difference; novelty.